Prevention of Type II diabetes in subjects with impaired glucose tolerance : The Diabetes prevention study (DPS) in Finland: Study design and 1-year interim report on the feasibility of the lifestyle intervention programme - ERIKSSON, J; LINDSTRÖM, J; LEHTONEN, A; LOUHERANTA, A; MANNELIN, M; MARTIKKALA, V; RASTAS, M; SUNDVALL, J; TURPEINEN, A; VILJANEN, T; UUSITUPA, M; TUOMILEHTO, J; et al. (Diabetologia, 1999)
AIMS/HYPOTHESIS; The aim of the Diabetes Prevention Study is to assess the efficacy of an intensive diet-exercise programme in preventing or delaying Type II (non-insulin-dependent) diabetes mellitus in subjects with impaired glucose tolerance, to evaluate the effects of the intervention programme on cardiovascular risk factors and to assess the determinants for the progression to diabetes in persons with impaired glucose tolerance. A total of 523 overweight subjects with impaired glucose tolerance ascertained by two oral glucose tolerance tests were randomised to either a control or intervention group. The control subjects received general information at the start of the trial about the lifestyle changes necessary to prevent diabetes and about annual follow-up visits. The intervention subjects had seven sessions with a nutritionist during the first year and a visit every 3 months thereafter aimed at reducing weight, the intake of saturated fat and increasing the intake of dietary fibre. Intervention subjects were also guided individually to increase their physical activity. During the first year, weight loss in the first 212 study subjects was 4.7 +/- 5.5 vs 0.9 +/- 4.1 kg in the intervention and control group, respectively (p < 0.001). The plasma glucose concentrations (fasting: 5.9 +/- 0.7 vs 6.4 +/- 0.8 mmol/l, p < 0.001; and 2-h 7.8 +/- 1.8 vs 8.5 +/- 2.3 mmol/l, p < 0.05) were significantly lower in the intervention group after the first year of intervention. Favourable changes were also found in blood pressure, serum lipids and anthropometric indices in the intervention group. The interim results show the efficacy and feasibility of the lifestyle intervention programme.